Out-of-hospital cardiac arrest in pregnant women: A 55-patient French cohort study. (October 2022) - Canon, Valentine; Recher, Morgan; Lafrance, Martin; Wawrzyniak, Perrine; Vilhelm, Christian; Agostinucci, Jean-Marc; Thiriez, Sylvain; Mansouri, Nadia; Morel-Maréchal, Emanuel; Lagadec, Steven; Leroy, Antoine; Vermersch, Céline; et al.
Abstract: Aim: To describe a cohort of pregnant women having suffered an out-of-hospital cardiac arrest (OHCA) and to compare them with nonpregnant women of childbearing age having suffered OHCA. Methods: Study data were extracted from the French National OHCA Registry between 2011 and 2021. We compared patients in terms of characteristics, care and survival. Results: We included 3, 645 women of childbearing age (15–44) who had suffered an OHCA; 55 of the women were pregnant. Pregnant women were younger than nonpregnant victims (30 vs. 35 years, p  = 0.006) and were more likely to have a medical history (76.4% vs. 50.5%, p  < 0.001) and a medical cause of the OHCA (85.5% vs. 57.2%, p  < 0.001). Advanced Life Support was more frequently administered to pregnant women (98.2%, vs. 72.0%; p  < 0.001). In pregnant women, the median time of MICU arrival was 20 minutes for the Medical Intensive Care Unit with no difference with nonpregnant women. Survival rate on admission to hospital was higher among pregnant women (43.6% vs. 27.3%; p  = 0.009). There was no difference in 30-day survival between pregnant and nonpregnant groups (14.5% vs. 7.3%; p  = 0.061). Fetal survival was only observed for OHCAs that occurred during the pregnancy second or third trimester (survival rates: 10.0% and 23.5%, respectively). Conclusions: Our results show that resuscitation performance does not meet European Resuscitation Council's specific guidelines on OHCA in pregnant women. Although OHCA in pregnancy is rare, the associated prognosis is poor for both woman and fetus. Preventive measures should be reinforced, especially when pregnant women have medical history.